Sharing ownership, profits, and decision-making in the 21st century - Kruse, Douglas; Emerald eBooks (Bingley, U.K. : Emerald, 2013)
Ownership and decision-making are key issues in the economic restructuring taking place as economies struggle to emerge from the Great Recession, and technological change and globalization continue to place new demands on workers and firms. Corporate, labor, and policy leaders are increasingly recognizing the potential role of employee ownership, cooperatives, profit sharing, and other ways in which employees directly participate in decision-making and financial performance. This volume contains cutting-edge research on the causes and effects of financial and decision-making participation, including results from the United States, European Union, Russia, India, and Basque area of Spain, along with a unique laboratory experiment to probe the real-world findings. Along with consideration of standard economic outcomes are studies that examine job satisfaction in the largest U.S. worker cooperative, and firm survival among cooperatives and ESOP companies. In addition, there are theoretical and thought pieces on the meaning and value of employee ownership in a rapidly changing world economy.
Effects of cooperative membership and participation in decision making on job satisfaction of home health aides / Daphne P. Berry -- Can group-incentives without participation survive the free-rider problem? A view from the lab / Philip Mellizo -- Information technology and high performance workplace practices : evidence on their incidence from upstate New York establishments / Derek C. Jones, Jeffrey Pliskin -- The relative survival of worker cooperatives and barriers to their creation / Erik K. Olsen -- Firm survival and performance in privately held ESOP companies / Joseph Blasi, Douglas Kruse, Dan Weltmann -- What does Mondragon teach us about workplace democracy? / Tom Malleson -- Employee ownership in Russia : evolution and current status / Tatiana Kachalina (Ershova) -- Determinants of financial participation in the EU : employers' and employees' perspectives / Iraj Hashi, Alban Hashani -- Financial and decision-making participation of marginalized small farmers through the Pragathi Bandhu model in India / Sudha Kornginnaya -- Democratic differences : how type of ownership affects workplace democracy and its broader social effects / Mark J. Kaswan -- The labor managed firm : a theoretical model explaining emergence and behavior / Anthony Jensen -- Three themes about democratic enterprises : capital structure, education, and spin-offs / David Ellerman -- Political metaphors and workplace governance / Christopher Mackin -- Worker ownership and collaborative production / Charles Heckscher -- Destructive trade and workers self-defense through economic democracy : a research note / Jaroslav Vanek.
Includes index.
Keywords: Business & Economics -- Accounting -- General; Business & Economics -- Accounting -- Managerial; Accounting; Finance & accounting; Management -- Employee participation; Electronic books